Study of Molecular Docking of Chalcone Analoque Compound as Inhibitors for Liver Cancer Cells HepG2 - Neni Frimayanti; Enda Mora; Rizki Anugrah (Computer Engineering and Applications Journal, 2018)
Molecular docking study using chalcone analogue compounds with proteins target from modeling crystallographic structure of Tyrosine kinase enzymes with code 1T46 was carried out with the aid of a computer using the AutoDock Vina program. The aim this study to determine the activity of 5 chalcone analogue compounds obtained from previous studies and 3 chalcone analogues which were modified as inhibitors of liver cancer using 5-fluorouracil as a positive control. Based on the docking results, it has been carried out and shown those compounds 1, 2, and 3 have the potential as the active inhibitors againts HepG2 liver cancer with a successive affinity of -10.1 kcal/mol, -9.7 kcal/mol, and - 9.6 kcal/mol, respectively. For the modified chalcone analogue compounds, compound 8 has the best results with an affinity value of -8.3 kcal/mol and this compound also has six amino acid residues which are the same as 5-flourouracyl (i.e. positive control).